Longitudinal variability of diazotroph abundances in the subtropical North Atlantic Ocean - Benavides, Mar; Moisander, Pia H.; Daley, Meaghan C.; Bode, Antonio; Aristegui, Javier (Journal of Plankton Research, 2016)
Diazotrophy-related studies in the North Atlantic have largely focused on its western tropical area, leaving the subtropics and the east undersampled. We studied the longitudinal distribution of Trichodesmium, UCYN-A, UCYN-B, the putative Gammaproteobacterium γ-24774A11 and Richelia (Het1) along 24.5N, using quantitative polymerase chain reaction on different size fractions (10, 10-3 and 3-0.2 μm) and additional filament counts for Trichodesmium. Trichodesmium was the most abundant phylotype, followed by UCYN-A, γ-24774A11 and Het1, with maximum abundances of 8.8 × 105, 2.0 × 105, 3.3 × 103 and 3.4 × 102 nifH copies L-1, respectively, whereas UCYN-B was mostly undetected. A clear shift in the diazotroph community was observed at ~30°W, coinciding with the transition between the North Atlantic Subtropical Gyre boundary and inner core. This transition zone divided the transect into an eastern half dominated by UCYN-A and western half dominated by Trichodesmium and γ-24774A11. γ-24774A11 was only detected in the 10-3 μm fraction, suggesting their association with larger microbes or aggregates. Our results indicate that typical size fractionation by 10 mm is not optimal for reconciling diazotroph phylotypes to N2 fixation rates and that non-cyanobacterial diazotrophs may contribute importantly to bulk diazotrophic activity in the western subtropical North Atlantic.